Resin-modified glass ionomer containing calcium glycerophosphate: physico-mechanical properties and enamel demineralization - Sâmia Sass SANTOS; Alberto Carlos Botazzo DELBEM; João Carlos Silos MORAES; José Antônio Santos SOUZA; Lenara Queiroz Chaves OLIVEIRA; Denise PEDRINI (University of São Paulo, 2019)
Abstract Sources of calcium and phosphate have been added to dental restorative materials to improve their anticaries effect. Objective This study evaluated the effect of adding calcium glycerophosphate (CaGP) to resin-modified glass ionomer cement (RMGIC) on the physico-mechanical properties, ion release, and enamel demineralization. Material and Methods: Specimens were fabricated for each experimental group: RMGIC without CaGP (Control), RMGIC with 1, 3 and 9% CaGP. To determine the release of fluoride (F), calcium (Ca) and phosphorus (P), six specimens were immersed in demineralization and remineralization solutions for 15 days. In another experimental trial, the following physico-mechanical properties were evaluated at time intervals of 1 and 7 days after fabrication: compressive strength (n=12), diametral tensile strength (n=12), surface hardness of material (n=6) and the degree of conversion of monomers (n=8). To study enamel demineralization, specimens (n=12) were attached to enamel blocks and submitted to pH-cycling. Subsequently, surface and cross-sectional hardness and the concentration of F, Ca and P in enamel were determined. Results The addition of CaGP to RMGIC led to higher mean release of F, Ca and P when compared with control (p<0.001). Mechanical properties were within the range of those of the ionomer cements after addition of 1% and 3% CaGP. The degree of conversion did not differ between groups at the 1st and the 7th day (p>0.439). The addition of 3% and 9% CaGP reduced mineral loss and increased F, Ca and P in the enamel when compared with control (p<0.05). Conclusion The addition of 3% CaGP in RMGIC increased the release of F, P and Ca, reduced enamel demineralization, and maintained the physico-mechanical properties within the parameters for this material.